The influence of the use of stabilizer bracelet in a child with choreoathetoid cerebral palsy - Lucareli, Paulo Roberto Garcia; Oliveira, Danieli M; Lima, Mario Oliveira; Lima, Fernanda Púpio Silva; Artilheiro, Mariana Cunha; Oliveira, Claudia Santos; Corrêa, João Carlos Ferrari; Braccialli, Lígia Maria Presumido [UNESP] (My University, 2010)
Introduction: The use of stabilizer bracelet is a frequent treatment for movement disorders to strengthen muscles and adjust coordination. Still questions remain regarding the benefi t of using loads to decrease involuntary movements and the best load and placement. Objective: To measure the infl uence of the stabilizer bracelet on the kinematics and spatiotemporal parameters in planar movements performed by the upper limb. Method: One child, who has the spastic diplegy type of cerebral palsy with choreoathetoid component, and a control child without cerebral palsy, both female and 7 years old, were subjected to analysis of movements in relation to displacement, velocity, linear acceleration, and the calculation of mean square error (MSE) with and without use of stabilizer bracelet with loads of 25, 50, and 75% of the supported maximum load. Results: After comparing data between subjects, a difference was found between patient and control in all situations and variables. An inter-individual comparison using 25% of the maximum load showed the smallest difference with the NDE. Discussion and Conclusion: This therapeutic option is low cost, easy to apply, and does not signifi cantly interfere in the aesthetic of the individual. Therefore, physiotherapists may prescribe this for activities that require greater control of the upper limb because for the case studied the upper limb movement was more effi cient with the use of the stabilizer bracelet.

Introdução: O uso da pulseira estabilizadora é frequente no tratamento de distúrbios de movimento para fortalecer os músculos e ajustar coordenação. Ainda persistem dúvidas em relação à utilização de cargas para diminuir movimentos involuntários e as melhores cargas e posicionamentos.Objetivo: Avaliar a infl uência da pulseira estabilizadora na cinemática e nos parâmetros espaço-temporais em movimentos planares realizados pelo membro superior. Método: Uma criança, que apresenta diplegia com componente coreoatetóides devido a paralisia cerebral espástica,e uma criança controle sem paralisia cerebral, mesmo sexo, feminino e 7 anos de idade, foram submetidas à análise de movimentos em relação ao deslocamento, velocidade, aceleração linear e o cálculo do erro quadrado médio (MSE) com e sem a pulseira estabilizadora com cargas de 25, 50, e 75% da carga máxima suportada. Resultados: Após a compararação dos dados entre os sujeitos, foi observada diferença entre paciente e controle em todas as situações e variáveis. Uma comparação inter-individual, utilizando 25% da carga máxima apresentou a menor diferença com o EQM. Discussão e Conclusão: Esta opção terapêutica é de baixo custo, fácil aplicação e não interfere na estética do indivíduo. Portanto, os fi sioterapeutas podem prescrever esta modalidade para atividades que exigem maior controle do membro superior, porque para o caso estudado os movimentos dos membros superiores foram mais efi cientes com o uso da pulseira estabilizadora.
A Influência da Pulseira Estabilizadora em Uma Criança com Paralisia Cerebral Coreoatetóide
Keywords: cerebral palsy; kinematics; biomechanics; Exercise Movement Techniques; rehabilitation